Autoignition of sustainable fuels under dual operation with H2-carriers in a constant volume combustion chamber. (1st May 2023) - Hernández, Juan J.; Cova-Bonillo, A.; Ramos, A.; Wu, H.; Rodríguez-Fernández, J.
Highlights: The low reactivity fuel does not affect the onset of the low-temperature heat release. Main ignition delayed with the low reactivity fuel content, the effect of NH3 being more relevant. As the cetane number of the base fuel increases, the effect of the low reactivity fuel on ignition decreases. Autoignition of esters is less sensitive to dual-fuel operation than that of ethers and alcohols. Abstract: The expected increase in the use of environmentally friendly liquid fuels in medium and heavy-duty compression ignition engines (for both off-road and transport applications), together with the well-documented benefits of hydrogen-carriers to decrease energy dependence and to achieve a neutral-carbon economy (internal combustion engines highly contributing to the global CO2 emissions), have motivated this work. The autoignition characteristics of different alternative diesel-type fuels (hydrotreated vegetable oil, advanced biodiesel and blends of conventional diesel fuel with polyoxymethylene dimethyl ether and 1-butanol) under dual-fuel operation with H2, NH3, and CH4 were studied in a constant volume combustion chamber at 535 and 600 °C. The high reactivity fuel was replaced by the gaseous fuel up to 40 % by energy. The main ignition delay time was significantly affected not only by the type of low reactivity fuel, with ammonia considerably retarding autoignition, but also by the nature of the liquid fuel, biodiesel being the less sensitive to the presence of the H2 -carrier fuel. Results also proved that the higher the reactivity of the diesel-type fuel (quantified through the cetane number), the lower the influence of the gaseous fuel on the autoignition time.